أثر الإصلاح الضريبي على الاستثمار في سورية - صقر, محمد; علي, حسين; درويش, هنادي (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This study is about the impact of tax reform in Syria on investment during the period (2000-2010), based on a series of annual data on taxes and investment , issued by the Central Bureau of Statistics and the Ministry of Finance. These data were analyzed according to the SPSS program. This study showed that tax reform was one of the reasons for increased investment (Especially the private investment), and this was the result of a clear reduction in income tax rates (such as profit tax) and give more tax incentives. The analytical results showed a statistically significant effect of the taxes on investment in Syria, according to a very strong relationship with a correlation coefficient of high value. تناول البحث الحالي دراسة أثر الإصلاح الضريبي في سورية على الاستثمار خلال الفترة (2000-2010) بالاعتماد على سلسلة بيانات ثانوية سنوية للضرائب والاستثمار صادرة عن المكتب المركزي للإحصاء ووزارة المالية، وتم تحليل هذه البيانات وفق برنامج SPSS ، حيث بينت هذه الدراسة إسهام الإصلاح الضريبي في سورية خلال الفترة المدروسة في زيادة الاستثمار(وخاصة الاستثمار الخاص)، نتيجة لتخفيض واضح لمعدلات ضرائب الدخل (وأهمها كانت ضريبة الأرباح) وترافقت هذه الخطوة بتقديم المزيد من الحوافز الضريبية من مزايا وإعفاءات عديدة، كما بينت النتائج التحليلية وجود أثر ذو دلالة إحصائية لإجمالي الضرائب والرسوم على الاستثمار في سورية، وفق علاقة متينة جداً .